COVID-19 vaccine hesitancy among a rural and urban population in South India: A community-based cross-sectional study - Saravanan Vaithiyalingam; Sumedha Kesavan; Murugan Vengadesan; Kannadasan Karuppaiah (Journal of Clinical and Scientific Research)
Background: This pandemic has been accompanied by an overabundance of misinformation, ‘infodemic’ on a global scale. The objective of the study is to explore the attitude and hesitancy of rural versus urban adults (>18 years) towards the severe acute respiratory syndrome coronavirus-2 disease (COVID-19) vaccine. Methods: A community-based analytical cross-sectional survey was conducted in rural and urban field practice area. Systematic random sampling technique was applied; face-to-face interview was conducted amongst 523 participants. The World Health Organization Strategic Advisory Group of Expert on Immunisation (SAGE) questionnaire was used. Results: Amongst the total participants (n = 523), 274 participants were from rural area. Amongst the rural participants, majority of the participants were male 149 (54.4%), nearly 238 (86.9%) were married and 211 (77%) belonged to nuclear family. It was found from urban 94% of the participants and 53.6% from rural were reluctant to COVID-19 vaccine. One of the important factors which gives pressure and prevents them from get vaccinated were found to be stigma and it was more common in urban (66.6%) when compared to rural (13.9%) and the family members (16.1%) were another factor of participants for not taking the vaccine. Other reasons were side effects and fear death due to vaccine from urban and rural were 50%, 19.3% and 4.8%, 13.5%, respectively. Conclusions: Intense behaviour change interventions must focus on trust building through active community engagement, social mobilisation and transparent dissemination of vaccine-related information.